Process Types of Transitivity in Recount text written by Eleventh graders of ISAT-U Senior High School Philippines in Academic year 2018/2019 - Umi Rahmawati (Faculty of Education and Teachers Training, 2019)
AbstractThis study is conducted to analyze transitivity process used in eleventh graders students of ISAT-U Senior High School based on Halliday's theory of Systemic functional linguistic, and identify the most dominant process used in the text. This study focuses on analyzing students transitivity process in their writing. It is expected to give a students' insight understanding in using transitivity process in delivering their ideas through text.This study is classified into descriptive qualitative research. The subject of the research is 11 recount text from eleventh graders of ISAT-U Senior High School Philippines, while the unit analysis is clause on students writing. The writer collected the data through documentation. After reducing, the writer analyze the transitivity process found using Halliday's theory.The result of the study shows that there are six types of transitivity process used by the students in their writing, they are material process (41.80%), relational attributive (28.79%), mental process (11.76%), verbal process (10.53%), relational identifying process (3.10%), behavioral process (2.48%), and existential process (1.55%). Relational attributive and identifying are types from relational process. Based on the findings, students are able to apply six types of transitivity process in their writing. On the whole, material process positioned as the most dominant process used by students in delivering their idea. It is clearly shown by the percentage in which used in 135 of 323 clauses.